Dynamics of trust in institutions, the legitimacy of the social order, and social open innovation - Didenko, Nikolay I.; Romashkina, Gulnara F.; Skripnuk, Djamilia F.; Kulik, Sergei V. (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This article analyses the dynamics of trust in institutions, which underpin the legitimacy of social order, on the basis of a study of the developed Arctic region during the period 2006-2018. The authors considered the principal theoretical concepts on which the study of trust, the well-being of citizens, the assessment of security and compliance with the fundamental rights and freedoms of citizens is to be based. It is assumed that the legitimacy of the social order consists in a state where people not only trust specific institutions, but also enjoy a sense of security from threats and the ability to exercise basic rights and freedoms in the presence of a competent authority to protect them in case of violations. The dynamics of the security of the inhabitants of the region, associated with an increase in the level of their well-being, are considered. The structure for retaining the legitimacy of the social order is demonstrated on the basis of a number of indices and model calculations. Configuration analysis was carried out to support the construction of multidimensional models. It was concluded that there has been a dramatic collapse in the social activity of the inhabitants of the Arctic region bordering on social apathy. It is shown that, during the period under study, trust in local authorities significantly declined, while the importance attributed to respecting private property rights increased. Trust in social institutions is shown to be significantly lower than trust in government institutions, contradicting the situation in developed countries. It is recommended that more attention be paid to the functioning of local and municipal authorities governing the Arctic region, who are much more aware of the needs of the inhabitants since they are connected by much denser social ties. The authors substantiate the need to introduce social innovation that allows to diversify communication channels between the government and the public, meet unsatisfied social needs that are not solved by existing ...